2020
DOI: 10.1002/adma.202000128
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid‐Like Protein Aggregates: A New Class of Bioinspired Materials Merging an Interfacial Anchor with Antifouling

Abstract: Surfaces that resist nonspecific protein adsorption in a complex biological milieu are required for a variety of applications. However, few strategies can achieve a robust antifouling coating on a surface in an easy and reliable way, regardless of material type, morphology, and shape. Herein, the preparation of an antifouling coating by one‐step aqueous supramolecular assembly of bovine serum albumin (BSA) is reported. Based on fast amyloid‐like protein aggregation through the rapid reduction of the intramolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(164 citation statements)
references
References 71 publications
2
162
0
Order By: Relevance
“…After the water rinse, E. coli was removed from the surface of PCPTifs-1.5 membranes (Figure 4e), indicating its excellent bacteria antifouling property. [40] Therefore, we concluded that the enhanced antibacterial activity of PCPTifs-1.5 membranes is due to the synergistic antibacterial effect of chitosan and Tifs.…”
Section: (7 Of 9)mentioning
confidence: 87%
“…After the water rinse, E. coli was removed from the surface of PCPTifs-1.5 membranes (Figure 4e), indicating its excellent bacteria antifouling property. [40] Therefore, we concluded that the enhanced antibacterial activity of PCPTifs-1.5 membranes is due to the synergistic antibacterial effect of chitosan and Tifs.…”
Section: (7 Of 9)mentioning
confidence: 87%
“…The antifouling properties of BSA amyloid-like are related to the balance of positive and negative charges on the albumin protein surface. However, no evident antifouling capacity was observed for the other amyloidlike films prepared from lysozyme, insulin, and α-lactalbumin 49 . Although lysozyme amyloid fibrils, compared to their monomer, exhibit better antibacterial activities against both Staphylococcus aureus and Escherichia coli bacteria 100 , to endow a complete antifouling surface further modification is still desirable.…”
Section: Boxmentioning
confidence: 91%
“…BSA, the main protein of plasma, plays a pivotal role in blood as a carrier for many small molecules such as calcium and bilirubin. It also maintains the blood pH and oncotic pressure 49 . BSA is a cheap protein since large quantities are easily derived from bovine blood, a by-product of the cattle industry 50 .…”
Section: Protein Nanofibrils As New Water Purification Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a typical protein, BSA possesses the advantages of low cost, availability, high solubility in water, and good ligand-binding properties and is therefore one of the most frequently used components to construct biocompatible hydrogels. [27,28] The other chosen material was the inorganic salt NaCl, which appears to play a key role in the solubilization of myofibrillar proteins for subsequent denaturation/aggregation to give good water-holding capacity and acceptable elasticity of the resulting hydrogels. [29] However, poor mechanical properties are one of the major defects that limit the practical applications of BSA hydrogels.…”
mentioning
confidence: 99%